REGULATION OF FAKE NEWS: NATIONAL AND INTERNATIONAL REGULATIONS TO FIGHT FALSE NEWS - José Rabelo França, Alexsandro; Costa Camarão, Felipe (Revista Gênero e Interdisciplinaridade, 2022)
Cybernetic space, virtual environment materialized through the use of modern means of information and communication, has an immense amount of content, arranged in a chaotic and often anonymous way, making it difficult to filter out reliable sources. A favorable scenario for the multiplication of misinformation, which appears as one of the great evils of the new century, and one of its tentacles, the fake news. This work intends to evaluate, by analyzing the laws that deal with cyber crimes, if the legal framework presented today in Brazil is prepared to deal with the complexity of the fake news threat and if abroad there are good practices that can be brought to the country. It will use the hypothetical-deductive method as a basic method, using exploratory and qualitative research, with bibliographic research as a procedure, using current legislation, both Brazilian and foreign. As result of the research, it’s observed that the existence of international regulations that pacify both the understanding and the conduction of this issue is essential for the current threat to be eliminated or, at least, lessened. And, among the strategies to contain fake news, checking or verifying facts, called fact-checking, was considered the most viable way to combat the range of information that proliferates without control in the digital world. Following this trend, Europe has been showing growth in the fact-checking movement and in Brazil the first agency was Lupa, in 2015. Other forms of regulation, such as content control and criminal sanctions, can also contribute to this situation. Even so, the effective fight against fake news will only take place when there is international cooperation in favor of the effectiveness and speed of the procedures adopted, curbing its genesis by observing efficient methods of investigation and identification, in addition to specific and simplified civil and criminal rites.